Assistência ao ciclo gravídico puerperal em municípios de faixa de fronteira do estado do Paraná - Ribeiro, Sara Alves (2017)
Maternal and child health requires special governmental action, given its priority. In this sense, women's healthcare at different stages of their lives, including the reproductive period, has led to health initiatives and policies in different spheres (municipal, state and federal), aimed at structuring, financing and organizing the attention to women's health in the pregnancy-puerperal cycle. During the years, advances have been observed in the attention to women during the reproductive period. In 2000, the Prenatal and Birth Humanization Program was implemented; and in 2011, the Cegonha Network. However, little is known about the health and welfare conditions of this public in regions of the international border area, including the state of Paraná. Based on retrospective data from the years 2000, 2010 and 2014, an ecological and descriptive study was carried out. The objective was to evaluate different parameters related to maternal and neonatal health care, considering the 139 municipalities in the range of international border, located at a distance of 150 km from the border of the state of Paraná. The DATASUS public database, specifically the Live Birth Information System, Mortality Information System, as well as the database of the Brazilian Institute of Geography and Statistics (2000 and 2010 census) was used. The following dependent variables were considered, based on the mother's municipality of residence: percentage of pregnant women with 7 or more prenatal visits; percentage of pregnant women with duration of gestation <31 weeks to 36 weeks; percentage of cesarean delivery; low birth weight rate (<2500 grams); maternal mortality ratio and coefficient of fetal deaths and early neonatal death rate. The spatial analysis was performed using the free softwares Geoda and QGIS programs, where the I Moran Global and clustering were evaluated, as well as, the LISA analysis. As a result, in the analyzed period, it was found that, on average, among the 139 municipalities analyzed, there was improvement in relation to the following parameters: increased coverage of prenatal visits (≥7 visits), decreased maternal mortality, decreased rate of fetal deaths and early neonatal mortality. On the other hand, on the average, there was worsening in relation to the following parameters: an increase in the proportion of cesarean deliveries, increased proportion of low weight live births and increased rate of prematurity of live births. Through the analysis of Global Moran, it was verified that all analyzed variables had significant positive spatial dependencies. Through the LISA analysis, the presence of high-high and low-low groups for each parameter was verified, through which, it was possible to verify that in the border region of Paraná, the municipalities of the following health regionals presented worse indicators of the pregnancy-puerperal cycle: 10th, 11th, 12th, 13th and 20th regional health. On the other hand, the municipalities of the 7th and 8th RS presented better indicators. It is concluded that despite the observed advances in care in the pregnancy-puerperal cycle, there is still a worrying scenario, together with the heterogeneity of the quality of care observed among the municipalities in the region.